EFFECTIVENESS OF SLUMP AND STRAIGHT LEG RISING STRETCHING FOR PAIN AND FUNCTIONAL ACTIVITIES IN CHRONIC MYOGENIC LOW BACK PAIN AT RSU. ISLAM KLATEN: A CASE REPORT - Widiatmi, Sri; Sari, Dwi Rosella Komala (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: The slump test is a neurodynamic test to evaluate the mechanosensitivity of neuromeningeal structures within the vertebral canal. The straight leg raising (SLR) is a provocation test that evidences radicular irritation in the lumbosacral region by lower limb flexion and can be due to multiple causes. Active stretching effectively reduces pain and improves function in adults with LBP (first degree) in sub-acute and chronic phases. Methods: This study was a case report that observed twelve patients with chronic LBP divided into two groups. Group 1 received slum and SLR stretching, while in the group 2 did not treated with stretching, however only got the SWD and TENS. The pain intensity and functional ability were evaluated after treatment by VAS and Oswestry scale respectively. Objective: To determine the effectiveness of slump and SLR stretching for reducing pain and increasing ADL in patients with chronic myogenic LBP. Results: Fifty patients with a diagnosis of chronic myogenic LBP, 12 patients met the inclusion criteria devided into 2 groups. 11 of 12 patients reported decreased pain and increased functional activity. There was a decrease in pain 9 points and an increase in the functional activity of 12.3% in the group 1. While in the group 2, there was a decrease in pain as 3 points and an increase functional activity 2.33% as well. Conclusion: Slump and SLR stretching can reduce pain and increase functional activity in chronic myogenic LBP patients, although the intervention was only given twice and few samples. Further research needs to be done by increasing the number of samples and training doses.